Tailor-made, linear, and “comb-like” polyester-based copolymers: Synthesis, characterization, and thermal behavior of potential 3D-printing/electrospinning candidates - Redondo, Franco Leonardo (2018)
Tailor-made, linear, and “comb-like” poly(ε-caprolactone)-based copolymers were synthesized by employing a combination of controlled polymerization techniques. Poly(dimethylsiloxane-block-ε-caprolactone) copolymers (SCL#) were synthesized by a combination of anionic and ring-opening polymerization (ROP), whereas “comb-like” poly(hydroxyethylmethacrylate-co-(hydroxyethylmethacrylate-graft-ε-caprolactone)-block-ε-caprolactone) (HEMACL#) were synthesized through simultaneous ROP and reversible addition fragmentation chain transfer (RAFT) polymerization. Copolymers were characterized by hydrogen nuclear magnetic resonance ( 1 H-NMR), size exclusion chromatography (SEC), and Fourier transform infrared (FTIR) spectroscopy. All polymers exhibited narrow molar masses distributions (M w /M n < 1 54), and their thermal properties were analyzed by isothermal crystallization kinetics (Avrami’s theory, by using differential scanning calorimetry (DSC)) and by employing modulated thermogravimetric analysis (MTGA). The macromolecular structure exerts a noticeable effect on the PCL block behavior when compared to the PCL homopolymer, at least for the temperature range studied (16–24 ° C): less differences in thermal properties were observed for linear block copolymers, whereas for “comb-like” graft copolymers their final crystallization capacity strongly depends on the presence of branches. For both sets of copolymers, the decrease in the resulting melting temperatures and the increase in the half-life crystallization time values might be useful processing parameters, particularly if these copolymers are planned for using as an alternative source of 3D printing or electrospinning materials.